POWER DYNAMICS THROUGH POLITENESS STRATEGIES IN STEVEN UNIVERSE: THE MOVIE (2019) - Villareal Mamengko; Olga A. Rorintulus; Imelda Lolowang (SoCul: International Journal of Research in Social Cultural Issues, 2025)
Politeness strategies play an important role in shaping communication, especially in media where characters’ interactions reflect broader social values. While much research has examined politeness in everyday conversations, limited attention has been given to animated films, particularly non-Disney productions like Steven Universe: The Movie. This study investigates how politeness strategies and power dynamics are employed by the two central characters, Steven and Spinel, based on Brown and Levinson’s (1987) theory of politeness. Using a qualitative method (Creswell & Creswell, 2018), the researcher analyzed the movie’s transcript and identified 76 utterances containing different politeness strategies. The findings indicate that, within Brown and Levinson’s framework, Off-record strategies were used most frequently (27 occurrences), reflecting the characters’ tendency to express emotional conflict through indirectness and implied meaning. Positive Politeness (19 occurrences) appeared when the characters attempted to build solidarity and maintain relationships, while Negative Politeness and Bald-on-record strategies (15 occurrences each) were employed in situations requiring caution or direct confrontation. These patterns show how Steven’s empathy-driven language and Spinel’s insecurity-driven responses shape their power negotiation throughout the film. Overall, the study demonstrates that politeness strategies not only reveal character traits but also reinforce the movie’s themes of reconciliation, forgiveness, and personal growth.